Progress in Industrial Mathematics at ECMI 2004 - Di Bucchianico, Alessandro; Mattheij, Robert M.M; Peletier, Marc Adriaan (The European Consortium for Mathematics in Industry, 2006)
ECMI has a brand name in Industrial Mathematics and organises successful biannual conferences. This time, the conference on Industrial Mathematics held in Eindhoven in June 2004 Mathematics focused on Aerospace, Electronic Industry, Chemical Technology, Life Sciences, Materials, Geophysics, Financial Mathematics and Water flow. The majority of the invited talks on these topics can be found in these proceedings. Apart form these lectures, a large number of contributed papers and minisymposium papers are included here. They give an interesting and impressive overview of the important place mathematics has achieved in solving all kinds of problems met in industry, and commerce in particular.